Study on Different Fractions of Organic Molecules in the Baltic Sea Surface Microlayer by Spectrophoto- and Spectrofluorimetric Methods - Drozdowska, Violetta; Kowalczuk, Piotr; Konik, Marta; Dzierzbicka-Glowacka, Lidia (Frontiers in Marine Science, 2018)
The sea surface microlayer (SML), created by surface active organic molecules (called: surfactants), is a highly active interface between the sea and the atmosphere. In this study we used the absorption and fluorescence analysis of organic matter collected in the SML and in subsurface layer, of 1 m depth, to describe the changes in molecular size and weight and the composition of surfactants. Data were collected during three research cruises in coastal zone and open waters of the Baltic Sea. The values of the CDOM absorption coefficient were higher in the SML about 29% (in the UV light) to 17% (in a blue spectral range), that reveal dominance of low molecular weighted CDOM molecules, absorbing in the UV light, in the SML. The spectral slope coefficients at different spectral ranges, SΔλ increased with salinity, while the slope coefficient for 350–400 nm reach lower values by 10.5% in SML compared to SS, caused by an effect of irradiation on the SML. The fluorescence intensities of the main peaks at Excitation Emission Matrix spectra belonging to the main fluorescing components of marine organic matter, called: A, C, M, T, were higher in SML by 41, 43, 41, and 14% compared to SS. The ratio of fluorescence intensities, (M + T)/(A + C) and humification index, HIX, in the SML were, respectively, higher by 17.9% and lower by 10.7% compared to SS. These relationships reveal more intensive process of in situ produced components in the SML as well as faster removal of humic components of high MW in the SML. We have observed an increase of spectral slope ratio, SR, (S275–295 > S350–400) with increasing salinity (from 4.5 to 7.94 of practical salinity), being proof that the samples acquire more marine in character. The SR increased with salinity 33.5 and 23.6% in the SML and SS, respectively, and their maximal values in open water were still maintained. The fluorescence intensity of all FDOM peaks decreased in the same salinity gradient. The decrease rate was higher in SML for the fluorescing peaks by 34, 36, and 26% for A, C, and M, respectively than in the SS. Decrease rate indicated the susceptibility to photochemical degradation of respective peaks. This effect was strongest for C, while T peak was almost unbleached. The fluorescence intensity decrease rate was smaller in SS what indicated shielding effect of the SML.